2013
DOI: 10.1007/s00431-013-2003-x
|View full text |Cite
|
Sign up to set email alerts
|

MEFV gene mutations in Turkish children with juvenile idiopathic arthritis

Abstract: These findings suggest that mutations of the MEFV gene may be responsible for rheumatic diseases other than FMF, and patients with JIA especially males, ANA negatives, and ERA subgroups should be screened for MEFV gene mutations in countries where FMF is frequent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 17 publications
0
13
0
2
Order By: Relevance
“…The same authors investigated polymorphisms in the IL1 gene cluster and toll like receptors 2 and 4 genes but did not find an association with ERA [99,100]. At least two studies have identified a high frequency of MEFV gene mutations among Mediterranean patients with ERA but without the classical symptoms of Familial Mediterranean Fever which is associated with homozygous mutations in MEFV [101,102]. …”
Section: Genetics Of Enthesitis-related Arthritis (Era)mentioning
confidence: 99%
“…The same authors investigated polymorphisms in the IL1 gene cluster and toll like receptors 2 and 4 genes but did not find an association with ERA [99,100]. At least two studies have identified a high frequency of MEFV gene mutations among Mediterranean patients with ERA but without the classical symptoms of Familial Mediterranean Fever which is associated with homozygous mutations in MEFV [101,102]. …”
Section: Genetics Of Enthesitis-related Arthritis (Era)mentioning
confidence: 99%
“…Females are much more frequently affected with almost all types of JIA [11]. The aetiopathogenesis of JIA is not entirely understood, but abnormal immunoregulation, cytokine production, immunogenetic predisposition and latent viral infection may be involved [12]. …”
Section: Introductionmentioning
confidence: 99%
“…As with adults, the commonest pattern (consistently about 70 %) was recurrent self-limiting attacks of monoarthritis affecting the lower limbs with a low risk of long-term damage and a suggestion that colchicine prophylaxis was joint protective [ 44 ]. In Turkish, children with JIA carriage of MEFV variants were increased particularly among ANA-negative subjects and boys [ 45 ].…”
Section: Juvenile Arthritismentioning
confidence: 95%